Superconducting radio-frequency resonator in magnetic fields up to 6 T - Ebrahimi, Mohammad Sadegh; Stallkamp, N.; Quint, Wolfgang; Wiesel, M.; Vogel, Manuel; Martin, A.; Birkl, G. (Review of scientific instruments, 2016)
We have measured the characteristics of a superconducting radio-frequency resonator in an external magnetic field. The magnetic field strength has been varied with 10 mT resolution between zero and 6 T. The resonance frequency and the quality factor of the resonator have been found to change significantly as a function of the magnetic field strength. Both parameters show a hysteresis effect which is more pronounced for the resonance frequency. Quantitative knowledge of such behaviour is particularly important when experiments require specific values of resonance frequency and quality factor or when the magnetic field is changed while the resonator is in the superconducting state.